Of meat, men and property: the troubled career of a convert nun in eighteenth-century Kiev - Sharipova, Liudmyla (Cambridge University Press, 2017)
The article is based on the case study of Sister Asklipiodata, a Jewish convert to Christianity, who became a member of the monastic community in one of Kiev’s Orthodox convents in the second half of the eighteenth century. It explores the ways in which the non-communal way of life in Eastern Orthodox convents impacted both upon the praxis of monastic existence within the convent walls, and the relations with the secular world without. Parallel to this consideration of a lasting centrality of property ownership in Orthodox female monasticism, the article addresses the largely neglected question of Jewish assimilation in the Russian Empire prior to the Partitions of Poland (1772–93), which brought the sizeable Jewish population of the Commonwealth’s eastern borderlands in immediate contact with the Russian state.